Change in vitamin D levels occurs early after antiretroviral therapy initiation and depends on treatment regimen in resource-limited settings - Fiona P. Havers (2018)
Study Background: Vitamin D has wide-ranging effects on the immune system, and studies suggest that low serum vitamin D levels are associated with worse clinical outcomes in HIV. Recent studies have identified an interaction between antiretrovirals used to treat HIV and reduced serum vitamin D levels, but these studies have been done in North American and European populations. Methods: Using a prospective cohort study design nested in a multinational clinical trial, we examined the effect of three combination antiretroviral (cART) regimens on serum vitamin D levels in 270 cART-naïve, HIV-infected adults in nine diverse countries, (Brazil, Haiti, Peru, Thailand, India, Malawi, South Africa, Zimbabwe and the United States). We evaluated the change between baseline serum vitamin D levels and vitamin D levels 24 and 48 weeks after cART initiation. Results: Serum vitamin D levels decreased significantly from baseline to 24 weeks among those randomized to efavirenz/lamivudine/zidovudine (mean change: -7.94 [95% Confidence Interval (CI) -10.42, -5.54] ng/ml) and efavirenz/emtricitabine/tenofovir-DF (mean change: -6.66 [95% CI -9.40, -3.92] ng/ml) when compared to those randomized to atazanavir/emtricitabine/didanosine- EC (mean change: -2.29 [95% CI -4.83, 0.25] ng/ml). Vitamin D levels did not change significantly between week 24 and 48. Other factors that significantly affected serum vitamin D change included country (p < 0.001), season (p < 0.001) and baseline vitamin D level (p < 0.001). Conclusion: Efavirenz-containing cART regimens adversely affected vitamin D levels in patients from economically, geographically and racially diverse resource-limited settings. This effect was most pronounced early after cART initiation. Research is needed to define the role of Vitamin D supplementation in HIV care.